"You have to get along". Family networks, informal economy and unemployment in postsocialist Croatia - Rubić, Tihana (Array, 2014)
Since the early 1990s in post socialist Croatia, a significant amount of social-economic and political changes have occurred which have affected the structure of the Croatian labour market. Unemployment, insecurity, both successes and failures to adapt to the new economic value system and its newly re-established relationships and requirements, has all influenced the individual and family life. My present interest in research concerns issues of post-socialistic unemployment and underemployment, the informal economy, and family assistance in Croatia. I am interested less in the diversity of scales of cost-effect considerations of bypassing the law and regulations, and more in the cultural and social logic behind practices of informal economy. I intend to find out how Croatian individuals and families have re-established a balance in their everyday lives while coping with changes in the diminished and restructured (formal) labour market, and the "crisis" in the Croatian economic system in general. How uncertainty, the possibility of “being replaced” in the formal labour market and an increase in social inequality have affected the lives of families and individuals in Croatian society from the 1990s until today? How long-term formal unemployment and activities in the informal sector shaped/are shaping the everyday people’s lives? A qualitative ethnographic research was conducted among once full-employed industrial workers and nowadays formally jobless persons who are active in the sphere of informal economy, in a residential area in the south-eastern suburban part of Zagreb over a period of three years, starting from 2007. Informal economy has been constantly present in their lives, both in socialism and postsocialism, notwithstanding huge changes that occurred on the macroeconomic level. The aim of this paper is therefore to preserve some insights into the ongoing analysis of structural characteristics and the logic behind locally situated social relations in the sphere of an informal economy.